Pulmonary-Renal Syndrome in the Elderly: Immunosuppressive Treatment – Case Report - Żerek, Marta; Sitarek, Gracjan; Płonka, Wojciech; Chruścicki, Damian; Bednarczyk, Paulina; Pelc, Marcin (Quality in Sport, 2024)
Pulmonary-renal syndrome is called alveolar hemorrhage accompanied by glomerulonephritis. The above condition can occur as a manifestation of ANCA-associated granulomatosis with vasculitis. The course of the disease varies from mild, limited inflammation to rapid progression with multi-organ changes that can be life-threatening. The mainstay of therapy is immunosuppression - both in the acute phase of the disease and after clinical improvement. Unfortunately, common causes of death in addition to complications of the disease include side effects of immunosuppressive treatment. A 72-year-old man is transferred to the Nephrology Unit for acute kidney injury of unclear etiology. On the basis of clinical examination, laboratory and imaging studies, a diagnosis of systemic small vessel inflammation with c-ANCA occupying the kidneys, lungs and intestines was made. Due to acute respiratory failure, the patient was transferred to the ICU, where renal replacement therapy, plasmapheresis, steroid pulses and cyclophosphamide were administered. After clinical improvement, it was decided to continue cyclophosphamide therapy and monitor blood IgG levels. Unfortunately, 4 months later, the patient died of multiple organ failure caused by septic shock of bacterial etiology. In the described case, age and comorbidities were the biggest risk factors for infectious complications of immunosuppression. The population is aging, so it is necessary to analyze the current standards of immunosuppressive treatment to improve the prognosis of the elderly.